Ecosophy Study on Environmental Pollution by Waste Productivity in Dili Municipality (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2025)
The changes and developments that created at the beginning of the 21st century have changed the way of life and the human mindset towards the existence of the environment. A concrete example is environmental pollution caused by improper waste disposal and management. Dili municipality can be categorized as the dirtiest city. This study aims to examine the other side of the lack of community participation in protecting the environment, namely the awareness of the importance of the reciprocal relationship between humans and the environment. The study used mixed methods in collecting and analyzing data. The results of this study show that people do not appreciate the environment as a place of interaction between living creatures which is comfortable and healthy. For this reason, the study of ecosophy in analyzing the level of waste productivity provides added value that complements the technical side of the waste management process.